Building a developmental toxicity ontology. Issue 6 (31st January 2018) - Baker, Nancy; Boobis, Alan; Burgoon, Lyle; Carney, Edward; Currie, Richard; Fritsche, Ellen; Knudsen, Thomas; Laffont, Madeleine; Piersma, Aldert H.; Poole, Alan; Schneider, Steffen; Daston, George
Abstract : Background: As more information is generated about modes of action for developmental toxicity and more data are generated using high‐throughput and high‐content technologies, it is becoming necessary to organize that information. This report discussed the need for a systematic representation of knowledge about developmental toxicity (i.e., an ontology) and proposes a method to build one based on knowledge of developmental biology and mode of action/ adverse outcome pathways in developmental toxicity. Methods: This report is the result of a consensus working group developing a plan to create an ontology for developmental toxicity that spans multiple levels of biological organization. Results: This report provide a description of some of the challenges in building a developmental toxicity ontology and outlines a proposed methodology to meet those challenges. As the ontology is built on currently available web‐based resources, a review of these resources is provided. Case studies on one of the most well‐understood morphogens and developmental toxicants, retinoic acid, are presented as examples of how such an ontology might be developed. Discussion: This report outlines an approach to construct a developmental toxicity ontology. Such an ontology will facilitate computer‐based prediction of substances likely to induce human developmental toxicity.